Ongoing Transmission Of Onchocerciasis In The Pru District Of Ghana After Two Decades Of Mass Drug Administration With Ivermectin And Comparative Identifcation Of Members Of The Simulium Damnosum Complex Using Cytological And Morphological Techniques. - Chikezie, F.M.; Veriegh, F.B.D.; Armoo, S.; Boakye, D.A.; Taylor, M.; Osei‑Atweneboana, M.Y. (Parasites & Vectors, 2024)
Background: Human onchocerciasis remains a public health problem in Ghana. Mass drug administration (MDA) Ivermectin (IVM) has reduced disease morbidity and prevalence, but the transmission of onchocerciasis remains ongoing in several endemic foci. We investigated parasite transmission in some endemic communities in Ghana that had received>18 rounds of annual MDA with IVM and determined the species composition of black fly (Simulium damnosum) vectors in these areas. Methods: Adult female black flies were collected using human landing catches and identified as either forest or savanna species using morpho-taxonomic keys. The adult flies underwent dissection to determine their parity and detect any O. volvulus larvae, followed by the calculation of entomological indices. Simulium damnosum s.l. larvae were collected and preserved in freshly prepared Carnoy’s fixative and were later used for cytotaxonomic studies. Results: A total of 9,983 adult flies were caught: 6,569 and 3,414 in the rainy and dry seasons, respectively. Black fly biting activities over the study period showed bimodal or trimodal patterns. The highest monthly biting rate (MBR) of 10,578.75 bites/person/month was recorded in July in Beposo, while the highest monthly transmission potential of 100.69 infective bites/person/month was recorded in Asubende in August. Morphological analysis of 2,032 fies showed that 99.8% (2,028) of the fies were savanna species, with only 4 (0.2%) adult fies being of the forest species. Cytogenetic studies on 114 black fly larvae revealed three cytospecies (Simulium damnosum s.s., S. sirbanum and S. sanctipauli) in the study area. Conclusions: The present studies confirmed an ongoing transmission of onchocerciasis in the study communities except Abua-1. It also provides further information on biting behaviors and onchocerciasis transmission indices in the study communities. Further, our data confirmed the savanna species (S. damnosum s.s. and S. sirbanum) of the S.
Research Article
Keywords: Onchocerciasis; Onchocerca volvulus; Simulium damnosum; Transmission; Black fies; Cytotaxanomy